2012
DOI: 10.3892/mmr.2012.1243
|View full text |Cite
|
Sign up to set email alerts
|

Alpinetin promotes Bax translocation, induces apoptosis through the mitochondrial pathway and arrests human gastric cancer cells at the G2/M phase

Abstract: Abstract. Alpinetin is a natural flavonoid widely distributed inZingiberaceae. Previous studies have demonstrated that alpinetin markedly inhibits tumour growth. However, the molecular mechanisms underlying the antitumour effects of alpinetin are unclear. Bcl-2-associated X protein (Bax) translocation is known to activate the mitochondrial-dependent endogenous apoptosis pathway. The aim of the current study was to investigate the roles of Bax and the mitochondrial pathway during alpinetin-induced gastric cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…1A) is a natural flavonoid primarily derived from the roots or seeds of Alpinia katsumadai Hayata that is known to exhibit antibacterial, anti-inflammatory and other important therapeutic properties (12)(13)(14)(15)(16)(17)(18). In previous studies, alpinetin was reported to inhibit proliferation of human tumor cells, including lung cancer and gastroenteric cancer cells (12)(13)(14)(15)(16)19), indicating the potential anticancer properties of this compound. However, the effects of alpinetin on ovarian cancer cells and its underlying mechanisms of action remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1A) is a natural flavonoid primarily derived from the roots or seeds of Alpinia katsumadai Hayata that is known to exhibit antibacterial, anti-inflammatory and other important therapeutic properties (12)(13)(14)(15)(16)(17)(18). In previous studies, alpinetin was reported to inhibit proliferation of human tumor cells, including lung cancer and gastroenteric cancer cells (12)(13)(14)(15)(16)19), indicating the potential anticancer properties of this compound. However, the effects of alpinetin on ovarian cancer cells and its underlying mechanisms of action remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A number of genes and proteins can influence or instigate the progression of apoptosis along the mitochondrial pathway (10). The most important genes associated with apoptosis are proteins of the Bcl family and caspases (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been shown to induce apoptosis and is suggested to be central to the apoptotic pathway (23,24). As a group of proteolytic enzymes at the end of the apoptotic signaling pathway, the caspase family plays an essential role in apoptosis.…”
Section: Discussionmentioning
confidence: 99%